Modifying the Poverty Reduction and Growth Trust (PRGT) Cumulative Borrowing Limit. (Policy Papers; Policy Paper ;, 2018)
An effort to mobilize SDR 11 billion in additional Poverty Reduction and Growth Trust (PRGT) loan resources is underway to sustain the Fund's concessional lending operations over the medium term. SDR 9.4 billion in new loan resources have been secured to date and negotiations with remaining potential loan providers indicate that the target is likely to be exceeded by about SDR 1\2 to 1 billion. To accommodate the better-than-expected loan mobilization outcome, the PRGT's cumulative borrowing limit of SDR 37 billion would need to be increased. PRGT creditors were consulted and supportive of a proposed increase in the borrowing limit, from SDR 37 billion to SDR 38 billion.